Footprint shape and component stiffness on rolling resistance of tyre - Pillai P S (Natural Rubber Research, 2004)
A combined analysis of the two equations for rolling resistance R, one based on the whole tyre hysteresis ratio and a second one based on the tyre spring rate, indicated that the tyre parameters namely, the hysteresis ratio (h), the footprint dimensions width (w) and area (A) and the radial stiffness (K) were the first order effects that affect the rolling resistance. The rolling loss reduction with reduced tread width was explained by the footprint shape term (w/A) rather than by the tyre weight loss values. The K was partitioned into component stiffness values. The K value was approximately equal to 8 per cent of tread stiffness K(t), 15 per cent of carcass stiffness K(c) and 75 per cent of inflation pressure stiffness K(a) for a P195/75R14 size tyre for its working pressure range (207-262kPa). The K(a) term was evaluated for the first time for this tyre.
Keywords: Component stiffness; Footprint shape; Rectangularity; Rolling resistance; Tyre